New Approach to the Limiter Functions (Journal of Computational Mathematics, 1999)
In this paper we discuss three topics on the designing of the limiter functions. (1) To guarantee the TVD property (2) To maintain enough artificial viscosity. (3) A method to form TVB limiter which can ensure second order accuracy even at the extrema of the solution.